2021
DOI: 10.1038/s41598-021-82878-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifications of immune-responsive genes for adaptative traits by comparative transcriptome analysis of spleen tissue from Kazakh and Suffolk sheep

Abstract: Aridity and heat are significant environmental stressors that affect sheep adaptation and adaptability, thus influencing immunity, growth, reproduction, production performance, and profitability. The aim of this study was to profile mRNA expression levels in the spleen of indigenous Kazakh sheep breed for comparative analysis with the exotic Suffolk breed. Spleen histomorphology was observed in indigenous Kazakh sheep and exotic Suffolk sheep raised in Xinjiang China. Transcriptome sequencing of spleen tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“… Yang et al (2021) demonstrated the levels of IgG and IL-1β were significantly higher in indigenous Kazakh sheep compared to Suffolk sheep, which grow quickly, but do not adapt to harsh environments and have lower levels of IgG and cytokines. Hence, they concluded that indigenous breeds may have a higher immunity and adapt more easily to stringent environmental conditions compared to Suffolk sheep ( Yang et al, 2021 ). Previous studies have demonstrated a higher expression of TLR-4, TLR-5 , and TLR-7 in the indigenous chickens of India compared to the White Leghorn ( Ramasamy et al, 2010 ; Haunshi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“… Yang et al (2021) demonstrated the levels of IgG and IL-1β were significantly higher in indigenous Kazakh sheep compared to Suffolk sheep, which grow quickly, but do not adapt to harsh environments and have lower levels of IgG and cytokines. Hence, they concluded that indigenous breeds may have a higher immunity and adapt more easily to stringent environmental conditions compared to Suffolk sheep ( Yang et al, 2021 ). Previous studies have demonstrated a higher expression of TLR-4, TLR-5 , and TLR-7 in the indigenous chickens of India compared to the White Leghorn ( Ramasamy et al, 2010 ; Haunshi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
“…The multivariate analysis also demonstrated that slow-growing birds in the free-range system had positive scores (i.e., high IL-6, IL-2 , and iNOS expression and low H/L ratio), whereas the fast-growing birds had negative scores (i.e., low IL-6, IL-2 , and iNOS expression and high H/L ratio), which confirmed that local breeds are characterized by a certain degree of adaptability toward the environmental conditions. Several authors have conducted a comparative analysis between indigenous and exotic ovine ( Yang et al, 2021 ) and chickens breeds ( Haunshi et al, 2017 ) in order to investigate their adaptability to environmental stressors by means of cytokine expressions. Yang et al (2021) demonstrated the levels of IgG and IL-1β were significantly higher in indigenous Kazakh sheep compared to Suffolk sheep, which grow quickly, but do not adapt to harsh environments and have lower levels of IgG and cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular breeds used for meat production include the Morada Nova, Santa Inês, Dorper, Suffolk, Poll Dorset, Texel, Ilê de France, and Hampshire breeds [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. As mentioned, the Morada Nova, Santa Inês, and Dorper varieties can be raised in any mesoregion of the state, based on the THI maps ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Hu sheep breed is highly regarded in China for its advantageous features of non-seasonal estrus, multiple births, tolerance to roughage, and suitability for domestic breeding [ 13 , 14 ]. Southdown sheep and Suffolk sheep have the characteristics of early development and easy fattening, and their rams are suitable for hybridization to obtain good growth and carcass characteristics [ 15 , 16 , 17 ]. Proteomics can be used to systematically characterize large-scale dynamic changes in protein expression [ 18 ], contributing to genomics and transcriptomics by deepening our understanding of complex biochemical processes at the molecular level [ 19 ].…”
Section: Introductionmentioning
confidence: 99%